2016
DOI: 10.1287/isre.2016.0635
|View full text |Cite
|
Sign up to set email alerts
|

Do Incentive Hierarchies Induce User Effort? Evidence from an Online Knowledge Exchange

Abstract: UGC (User-generated content) websites routinely deploy incentive hierarchies, where users achieve increasingly higher status in the community after achieving increasingly more difficult goals, to motivate users to contribute. Yet the existing empirical literature remains largely unclear whether such hierarchies are indeed effective in inducing user contributions. We gathered data from a large online crowd-based knowledge exchange to answer this question, and drew on the goal setting theory to study users' cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(82 citation statements)
references
References 52 publications
4
78
0
Order By: Relevance
“…Chau and Xu (2012) develop a framework capable of gathering, extracting, and analyzing blog information that can be applied to any organization, topic, or product/service. Goes et al (2016) study goal setting and status hierarchy theories to find that glory-based incentives motivate users to contribute more user-generated content only before/until the goal is reached, with the contribution dropping significantly later. examine Yahoo!…”
Section: Social Media and Participation In Online Communitiesmentioning
confidence: 99%
“…Chau and Xu (2012) develop a framework capable of gathering, extracting, and analyzing blog information that can be applied to any organization, topic, or product/service. Goes et al (2016) study goal setting and status hierarchy theories to find that glory-based incentives motivate users to contribute more user-generated content only before/until the goal is reached, with the contribution dropping significantly later. examine Yahoo!…”
Section: Social Media and Participation In Online Communitiesmentioning
confidence: 99%
“…This difference can be explained by a number of factors. First, research has found that men tend to exhibit lower risk aversion [19] and are more likely to be overconfident [44,45], because they focus primarily on success and pay less attention to failure [45]. It has therefore been found that competition increases the performance of men, but not women [46][47][48].…”
Section: Social Value Orientation Theory and The Role Of Gendermentioning
confidence: 99%
“…First, females have been found to exhibit more sociallyorientated traits. It has been found that females tend to feel more empathy [49] and exhibit greater sensitivity to social cues [19] and others' moods and affect [50]. Because females are more socially attuned, they are more likely to notice others' unfavorable circumstances [51], and thus are more likely, in turn, to respond to others' needs.…”
Section: Social Value Orientation Theory and The Role Of Gendermentioning
confidence: 99%
See 2 more Smart Citations